Reengineering for revenue growth - Angus, F. Raymond
F. Raymond Angus, Alan L. Goodman, Phil Pfund, Robert Wasson, Ralph Wyndrum and Walter M. Zoller examine the role of R&D in achieving corporate reengineering goals.
By partnering effectively with other corporate functions, R&D can help a company to achieve the innovation and revenue goals of its reengineering effort.
As more and more companies reengineer for revenue growth, R&D's value-added functions gain even greater importance. Successful companies today recognize that R&D is an important part of virtually every process in a company and must be included in overall reengineered processes. R&D has the resources and technical competencies to help a company implement more efficient processes and deliver more reliable products and services. Increasingly, R&D is viewed as a partner in achieving corporate reengineering goals. This article shares the findings and key learnings of a study group from the Quality Directors' Network of the Industrial Research Institute. The focus of the study group was to create a common understanding of business process reengineering, particularly for revenue growth, and the implications for R&D.
Keywords: Revenue growth